К вопросу об этногенезе удинского народа и уточнении термина «Страна Утийцев» - Айвазян, Григорий (ՀՀ ԳԱԱ հրատ.)
Հիմնվելով աղբյուրների նոր վերլուծության վրա՝ ներկայումս հնարավոր է պարզաբանել անտիկ շրջանից մինչև XI-XIII դդ. Կովկասյան Աղուանքում տեղի ունեցած էթնիկ գործընթացների հարցը: Հին և միջնադարյան աղբյուրների քննությունը ցույց է տալիս, որ լեզգիախոս քրիստոնյա աղուանների էթնոհամախմբման գործընթացը IX–X դարերում հաջողությամբ ավարտվեց Բուն Աղուանքի արևմուտքում միասնական ուդի ժողովրդի ձևավորմամբ, որը Շաքի-Հերեթի թագավորության ժամանակաշրջանում դարձավ երկրի գերակշռող ժողովուրդը: Ուդի էթնանունը այս ժամանակ արդեն դարձել էր լեզգիախոս քրիստոնյա աղուանների ինքնանունը, իսկ Աղուանք-Ալբանիա երկրի անունը՝ «Ուտէացւոց երկիր» հասկացության հոմանիշ: Proceeding from the analysis of available sources, we can now possibly clarify the nature of the ethnic interaction taking place in Caucasian Albania from ancient era up to the 10th–13th centuries. The analysis of the ancient and medieval sources shows that the ethno-consolidation of Lezgian-speaking Albanian Christians in the west of Caucasian Albania, successfully completed in the 9th–10th centuries, leading to the formation of Udi people, who became the dominant population in Caucasian Albania during the period of Shaki-Hereti's kingdom. The ethnonym "Udi" had by this time established itself as a self-denomination (endo-ethnonym) for practically all Lezgian-speaking Albanian Christians, and the name Ałvank (Albania) is synonymous to "the country of Utians”.
Keywords: История